The Efforts of the Society in Preserving Ngarot Art in Lelea Village, Indramayu Regency - ramayuda, rengga (Universitas Pasundan, 2025)
Abstract This research aims to identify and understand the factors that affecting the efforts to preserve the Ngarot art in Lelea Village, Indramayu Regency through an ethnographic approach. By using qualitative methods, this research focusing on the analysis of various elements that play a role in the continuity of tradition that. The Ngarot traditional ceremony, which involves the participation of the younger generation in activities agriculture and local culture, have a role that is greater than just entertainment. This ceremony serves as a medium to instill important values in life, such as mutual assistance, respect for ancestors, and social awareness. This conservation effort is strengthened by education based on local wisdom, training, arts, and the development of an active arts community. In addition, support the local government through facilities and participation in funding, thereby strengthening the preservation measures. The use of technology and social media also paving the way for this art to be more widely recognized, so that it can be sustainable continuously maintained as a symbol of local wisdom that thrives in Lelea Village.